Implementation of Basic Literacy Models for Elementary School Students - Bata, M. Banuri; Markhamah; Rahmawati, Laili Etika; Minsih; Choiriyah (International Journal of Elementary Education, 2023)
One of the efforts made by the government to implement an independent curriculum is to create a School Literacy Movement. This program is implemented to foster students' interest in reading and can improve reading skills to master knowledge better. Various obstacles arose regarding the implementation of the Basic Literacy Movement program in elementary schools. This study aims to analyze the coverage of the implementation of the basic literacy model in elementary schools. The method in this study uses a qualitative approach with an exploratory descriptive design. The source of data in this study is an elementary school. The data collection techniques are carried out by observation, and documentation. The data analysis techniques include data reduction, data display, and data verification. The test of validity data using technical triangulation. The results showed that the coverage of the implementation of the literacy model was 100%, the numeracy literacy model was 100%, the scientific literacy model was 50%, the digital literacy model was 64.10%, the financial literacy model was 41.02%, and the civics cultural literacy model was 100%. The conclusion in this study is that the basic literacy movement in elementary schools is carried out with several activities including literacy, numeracy, science, finance, digital, and culture. It is hoped that future research can pay more attention to literacy models that have not yet achieved basic literacy implementation, so that the embodiment of the school literacy movement can be achieved more proportionally and comprehensively.